Differences between Pre-School Children with and without Special Educational Needs Functioning, Participation, and Environmental Barriers at Home and in Community Settings: An International Classification of Functioning, Disability, and Health for Children and Youth Approach - Guichard, Sofia; Grande, Catarina (Frontiers in Education, 2018)
The International Classification of Functioning, Disability, and Health for Children and Youth (ICF-CY; WHO, 2007) provides a framework for child functioning with an emphasis on child participation. Participation is defined as “involvement in life situations” and can be influenced by both child characteristics (health conditions, body functions, and structures) and contextual factors (facilitators or barriers of the physical or social environment) (WHO, 2007). This study is aimed at characterizing the functioning of pre-school-aged children, based on their frequency of participation in home and community activities and on the perception of environmental barriers to their participation by parents, using an ICF-CY approach. Differences between children with Special Educational Needs (SEN) (n = 42) and children without SEN (n = 74) were analyzed. Parents of 116 children from the Porto District (Portugal) completed an adapted version of the Young Children’s Participation and Environment Measure (YC-PEM; Khetani et al., 2013a). To assess child functioning, pre-school teachers completed six items of the Matrix for Assessment of Activities and Participation (Castro and Pinto, 2015), corresponding to six code sets of the ICF-CY Developmental Code Sets (Ellingsen, 2011). Children with SEN showed lower levels of functioning when compared to children without SEN, according to their pre-school teachers. Parents of children with SEN reported that their children participated less frequently in home activities. Specifically, significant differences were found in household chores, at home. Parents of children with SEN perceived more environmental factors as barriers in both settings when compared to parents of children without SEN. Differences between groups in specific environmental factors are presented with reference to the YC-PEM environmental content linked to the ICF-CY environmental domains (Khetani, 2015). Findings highlight the importance of identifying and adjusting environmental barriers, through family-centered practices, to promote child participation and overall functioning. The adoption of the ICF-CY (WHO, 2007) is recommended when implementing and monitoring inclusive services and practices. Results are further analyzed and discussed with reference to the biopsychosocial model of the ICF-CY (WHO, 2007).